2008
DOI: 10.1007/s11999-008-0463-5
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Platform versus Fixed-bearing Total Knees: An In Vitro Study of Wear

Abstract: One of the assumed benefits of mobile bearings is the reduction of UHMWPE wear. However, to date, such benefit has not been categorically proven. To test the hypothesis that rotating platform total knee arthroplasty would have less wear than a fixed-bearing of the same design, this in vitro study compared the wear and kinematics (which influence wear) of one type of mobile with fixed-bearing tibial components of otherwise identical design. We tested four fixed bearing (FB) and four rotating platforms (RP) on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…23 Similar polyethylene wear was found for a mobile-bearing rotating platform and a fixed modular bearing in an in vitro study. 28 Another in vitro study, however, concluded that the wear rate of the fixed bearing was four times higher than for the rotating platform, 29 but in two meta-analyses no differences in the incidence of radiolucent lines or clinical outcome were found. 21,30 Recent reports from the NAR did not show differences in pain, function or survival for the LCS Classic, or survival for the LCS Complete, compared to the AGC Universal TKR.…”
Section: Discussionmentioning
confidence: 99%
“…23 Similar polyethylene wear was found for a mobile-bearing rotating platform and a fixed modular bearing in an in vitro study. 28 Another in vitro study, however, concluded that the wear rate of the fixed bearing was four times higher than for the rotating platform, 29 but in two meta-analyses no differences in the incidence of radiolucent lines or clinical outcome were found. 21,30 Recent reports from the NAR did not show differences in pain, function or survival for the LCS Classic, or survival for the LCS Complete, compared to the AGC Universal TKR.…”
Section: Discussionmentioning
confidence: 99%
“…crosslinked vs. conventional) (Muratoglu et al, 2007), the conformity of the inlay and the loading conditions (Galvin et al, 2009), as well as the implant concept (e.g. fixed vs. mobile) (Haider et al, 2008) have an effect on PE wear. Additionally implant kinematics are important.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the stiffness of these springs is often too high to represent a sectioned ligament, which commonly exists when implanting a TKR (Benson et al, 2001, Schwenke et al, 2005. Haider et al (2008Haider et al ( , 2002 proposed a triphasic spring model to simulate the knee laxity. They recommended a gap in the AP direction to remove stiffness around the neutral position.…”
Section: Discussionmentioning
confidence: 99%
“…The cautious approach for the efficiency of mobile bearing prostheses is even supported by the results of their biomechanical testing. It has been shown by a simulator based experiment, utilizing six million cycles of repetitive testing of prosthesis movement of mobile bearing designs with rotating platform and one fixed bearing implant, that there was no difference in the amount of in vitro wear (23).…”
Section: Introductionmentioning
confidence: 99%